(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the conceptual foundations of Key Performance Indicator (KPI) systems and their role in contemporary organizational management. Drawing on classical and modern management theories, including the Balanced Scorecard framework and performance measurement system literature, the study explores how KPIs function as strategic tools for aligning organizational activities with long term objectives. The research highlights core principles of KPI design, such as strategic alignment, balance, and adherence to SMART criteria, as well as the importance of validity and reliability in measurement systems. Furthermore, the article analyzes governance mechanisms, including ownership, monitoring processes, and integration into decision-making structures. Particular attention is given to common implementation challenges, such as misalignment with strategy, data quality issues, and insufficient managerial commitment. The study also investigates the impact of digital transformation on KPI systems, emphasizing the role of dashboards, real-time analytics, and emerging technologies in enhancing organizational performance. The findings suggest that well designed and effectively governed KPI systems significantly improve decision-making, accountability, and strategic execution in modern organizations.